Social Media Promotion, Tourism Facilities, and Price Effects on Revisit Intention: The Moderating Role of Visitor Satisfaction - Sherliya Sugiyanti; Rachmad Hidayat; Sri Rahayu (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the effect of social media promotion, tourism facilities, and price on revisit intention, with visitor satisfaction as a moderating variable at the Matahari Beach Fishing Spot, Sumenep Regency. A quantitative approach was employed using a survey method involving 120 respondents, with data collected through Likert-scale questionnaires. Data analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that social media promotion, tourism facilities, and price have a positive and significant effect on revisit intention. Furthermore, visitor satisfaction is proven to strengthen the influence of these variables on revisit intention. The findings of this study are expected to provide insights for tourism managers in formulating effective marketing and service strategies to enhance visitor satisfaction and encourage repeat visits.